ENVIRONMENTAL COMMUNICATION MANAGEMENT FOR NETWORK PARTNERS MAB TA PHUT INDUSTRIAL ESTATE OFFICE, RAYONG PROVINCE - Pianchobe, Wirat; Boonsiri, Kran; Panyawuttrakul, Haruthai; Thammaviphat, Kulthida (Journal of MCU Nakhondhat, 2025)
This research aimed to study: 1) Network partnership management for environmental communication; 2) Message content management for environmental communication; 3) Media production, dissemination, and evaluation management for environmental communication; and 4) Development guidelines for environmental communication management among network partners of the Map Ta Phut Industrial Estate Office, Rayong Province. A qualitative research method was employed. Data were collected through in-depth interviews with 27 purposively selected key informants who were directly involved in environmental communication management. The research instrument was a structured in-depth interview form, and the data were analyzed by synthesizing conclusions from the interviews. The findings revealed that: 1) Network partnership management involved a well-defined organizational structure, clearly assigned member roles, and the use of multiple communication technologies and channels combined with fieldwork, knowledge exchange, skill development, and the maintenance of relationships and trust. 2) Message content management emphasized quality and attractiveness, used clear and simple language, maintained appropriate scope, related content to the experiences and contexts of audiences, and controlled message intensity appropriately. 3) Media production, dissemination, and evaluation management included systematic planning and collaboration. Media were produced appropriately and disseminated through three main types of media: traditional media (newspapers, journals, posters) whose use has been declining; activity-based media (training, seminars, exhibitions) which proved highly effective; and online media (websites, Facebook, LINE) which were modern and easily accessible. Evaluation was conducted both formally and informally to enhance accuracy and reliability. 4) Development guidelines emphasized transparent network management, participation promotion, the creation of accurate and appealing content, the production and dissemination of modern media through diverse channels, and evaluation based on indicators reflecting genuine audience responses.